First evidence of cryptic species diversity and significant population structure in a widespread freshwater nematode morphospecies (Tobrilus gracilis). Issue 17 (9th August 2013) - Ristau, Kai; Steinfartz, Sebastian; Traunspurger, Walter
Abstract Free‐living nematodes are ubiquitous and highly abundant in terrestrial and aquatic environments, where they sustain ecosystem functioning by mineralization processes and nutrient cycling. Nevertheless, very little is known about their true diversity and intraspecific population structure. Recent molecular studies on marine nematodes indicated cryptic diversity and strong genetic differentiation of distinct populations, but for freshwater nematode species, analogous studies are lacking. Here, we present the first extensive molecular study exploring cryptic species diversity and genetic population structure of a widespread freshwater nematode morphospecies, Tobrilus gracilis, from nine postglacially formed European lakes. Taxonomic species status of individuals, analysed for fragments of the mitochondrial COI gene and for the large (LSU) and small (SSU) ribosomal subunits, were determined by morphological characteristics. Mitochondrial and nuclear markers strongly supported the existence of three distinct genetic lineages (Tg I–III) within Tobrilus gracilis, suggesting that this morphospecies indeed represents a complex of highly differentiated biological species. High genetic diversity was also observed at the population level. Across the nine lakes, 19 mitochondrial, and seven (LSU) and four (SSU) nuclear haplotypes were determined. A phylogeographical analysis revealed remarkable genetic differentiation even among neighbouring lake populations for one cryptic lineage. Priority and persistent founder effects are possible explanations for the observed population structure in the postglacially colonized lakes, but ask for future studies providing direct estimates of freshwater nematode dispersal rates. Our study suggests therefore that overall diversity of limnetic nematodes has been so far drastically underestimated and challenges the assumed ubiquitous distribution of other, single freshwater nematode morphospecies.